World trade organisation : a guide to the framework for international trade - Das, Bhagirath Lal (London, 1999)
This detailed and intelligible guide to the intricacies of the WTO Agreements which are rewriting wholesale the rules of economic intercourse between countries is for those negotiators, trade policy officials, executives in industry and students of international economic relations and commercial diplomacy who need to understand the new multilateral framework for world trade.
Keywords: Foreign trade